Beyond Latency: Chronic Toxoplasma Infection and Its Unveiled Behavioral and Clinical Manifestations—A 30-Year Research Perspective - Ashkan Latifi; Jaroslav Flegr (Biomedicines)
Over the past three turbulent decades, research has profoundly reshaped our understanding of chronic Toxoplasma gondii infection—traditionally regarded as harmless in immunocompetent individuals—unveiling its surprising impact on human health, performance, and behavior. This review emphasizes the effects of chronic Toxoplasma infection on physical and mental health, cognitive performance, and behavioral changes, highlighting key findings from studies investigating these domains, with a particular focus on both ultimate and proximate mechanisms underlying the observed effects. To this end, the primary focus will be on human studies; however, animal model studies will also be thoroughly considered when necessary and appropriate, to provide context and additional important information. Research demonstrates that chronic Toxoplasma infection may contribute to a broad spectrum of physical health issues. Ecological studies have revealed correlations between toxoplasmosis prevalence and increased morbidity and mortality from various conditions, including cardiovascular diseases, neurological disorders, and certain cancers. Large-scale cross-sectional studies have further shown that infected individuals report a higher incidence of numerous health complaints and diagnosed diseases, suggesting a significant impact on overall physical well-being. In addition to physical health, lifelong Toxoplasma infection (subclinical toxoplasmosis) has been implicated in cognitive impairments and behavioral changes. Studies have reported associations between infection and poorer performance in areas such as reaction time, processing speed, working memory, and executive function. Many of these behavioral changes likely relate to worsened health and a shift towards a “fast life history strategy.” These cognitive deficits can have significant implications for daily functioning and performance. Furthermore, the role of Toxoplasma infection in the development or exacerbation of mental health disorders has been extensively investigated. Meta-analyses, ecological studies, and large-scale observational studies have demonstrated associations between Toxoplasma infection and an increased risk of disorders such as schizophrenia and obsessive–compulsive disorder. While the precise mechanisms underlying these associations remain under investigation, research suggests that neuroinflammation and alterations in neurotransmitter systems are likely to play a role. Far from being harmless, subclinical toxoplasmosis is increasingly recognized as a hidden factor influencing human health, behavior, and cognitive performance—with implications that extend well beyond the individual to public health at large. Further research is warranted to elucidate the complex interplay between Toxoplasma infection, host physiology, and the development of various physical, cognitive, behavioral, and mental health conditions.